Role and Status of Women in Modern India - Pillai, A S (Journal of Dharma, 1986)
The Greek myth represents that human beings were originally composed of a man and a woman, that some god divided each being into two and these separated halves are continually searching for one another. To look upon husband and wife as complementaries which make up a whole is the true implication of married life. With this fact in mind, I approached the problem of women with the emphasis on the concept of equality between men and women in India. Before going straight into the topic, let us see the status of women in ancient India.